2006
DOI: 10.1177/1074840706296724
|View full text |Cite
|
Sign up to set email alerts
|

Swedish Families’ Lived Experience When a Child Is First Diagnosed as Having Insulin-Dependent Diabetes Mellitus

Abstract: Sweden has the second highest nationwide incidence of childhood diabetes in Europe, and it is rapidly increasing. The diagnosis of Type 1 insulin-dependent diabetes mellitus has been indicated as a crisis in the life of the individual and family. The purpose of this study was to elucidate the whole family's lived experience when a child in the family is diagnosed as having diabetes. It was designed as a longitudinal, descriptive, inductive study including qualitative interviews. Family members in 12 families w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0
15

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(117 citation statements)
references
References 51 publications
(39 reference statements)
5
97
0
15
Order By: Relevance
“…Perhaps efforts to improve feelings of recognition are taken more seriously with respect to environment rather than the lived body. However, facing and living with a chronic illness remains demanding, as was underscored by the participants in our studies; this findings is also in line with several other studies [30,59,60]. …”
Section: Discussionsupporting
confidence: 92%
“…Perhaps efforts to improve feelings of recognition are taken more seriously with respect to environment rather than the lived body. However, facing and living with a chronic illness remains demanding, as was underscored by the participants in our studies; this findings is also in line with several other studies [30,59,60]. …”
Section: Discussionsupporting
confidence: 92%
“…The impact of a diagnosis of T1D on children, parents and other family members can be significant due to the complex, invasive and relentless nature of diabetes management (Lowes, 2008;Wennick & Hallstrőm, 2006). The National Institute for Clinical Excellence (NICE) (2004) recommends a glycosylated hemoglobin (HbA 1c ) target of 58 mmol/mol (7.5%) or less.…”
Section: Type 1 Diabetes In Childhood and Adolescencementioning
confidence: 99%
“…In a systematic review, Whittemore, Jaser, Chao, Jang, and Grey (2012) revealed a prevalence of parental psychological distress at diagnosis of between 20% and 30%. Parents have described a feeling of being overwhelmed by the management demands, a feeling that persisted over time when experiencing the complexity of daily management, the constant fear of especially hypoglycaemic events and of new situations coming up (Smaldone & Ritholz, 2011; Sullivan-Bolyai et al, 2003; Wennick & Hallström, 2006). The fear of nighttime hypoglycaemia has been reported as extra challenging among parents of the youngest children (Monaghan, Hilliard, Cogen, & Streisand, 2009).…”
Section: Introductionmentioning
confidence: 99%